Systematic Literature Review: Penggunaan Metode Talking Stick Dalam Meningkatkan Hasil Belajar IPS di SMP - Putri Nursamsiyah; Sujarwo, Sujarwo (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
Education creates people who are civilized, intelligent, sensible, and virtuous so they can face the problems that exist in life. Educational success is influenced by several factors such as curriculum, students, teachers, school environment, and so on. The true learning process must be able to activate students, not just focus on the teacher. Students must be made the center of learning, meaning students must be actively involved in the learning process from beginning to end. In order for this to happen, teachers can carry out social studies learning by implementing the speaking stick learning method so that the class becomes active and students easily understand the material. The aim of this research is to identify the application of the speaking stick learning method to student learning outcomes in social studies lessons. This research uses the Systematic Literature Review (SLR) method to find the necessary data related to the research topic. The data that researchers obtained was based on secondary data sources originating from previous research articles. Based on a literature review, the author obtains an overview of the benefits and results obtained from implementing the speaking stick method in social studies learning, starting from increasing student learning activities and at the end of this learning, it is able to make students maximize their abilities and understanding so that there is an increase in social studies learning outcomes for students.